Exploring the usefulness of two variants of gaze-guiding-based dynamic job aids for performing a fixed-sequence start-up procedure after longer periods of non-use. (1st January 2014) - Kluge, Annette; Greve, Joseph; Borisov, Nikolaj; Weyers, Benjamin
Start-up procedures are non-routine tasks in process control, which are prone to skill decay. To mitigate skill decay, job performance aids (JPA) are used. A dynamic JPA was developed for the human-computer interface, which guides the gaze of the user by visual cues. Two gaze-guiding applications (spotlight, spotlight plus integration of information) were tested in terms of their impact in supporting the start-up performance after a three-week and six-month period of non-use ( N = 46). Irrespective of the gaze-guiding format, participants with three weeks of non-use outperform participants with six months of non-use. Results show that the best indicator of skill loss is the length of the period of non-use. It is assumed that the advantage of gaze guiding plus integration of information was not shown due to the loss of interface-operating knowledge. In conclusion, gaze guiding for long periods of non-use needs to be accompanied by interface-operating knowledge.